PERTUMBUHAN DAN PRODUKSI SAWI PAGODA (Brassica narinosa L.) PADA PEMBERIAN AB MIX DAN PUPUK ORGANIK CAIR PADA SISTEM HIDROPONIK RAKIT APUNG - Agrahaq, Sousa Virgi; Manurung, Adinda Nurul Huda; Ramdan, Evan Purnama (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Pagoda mustard (Brassica narinosa L.) is a leafy vegetable with high nutritional value, well-suited for hydroponic cultivation in limited land areas. Research on integrating Liquid Organic Fertilizer (LOF) and AB Mix (inorganic nutrients) in hydroponic systems generally aims to identify a nutrient management strategy that is balanced, cost-effective, and sustainable. This study evaluated the effects of varying AB Mix nutrient concentrations and foliar application of LOF on the growth and yield of pagoda mustard grown in a floating raft hydroponic system. The experimental design was a factorial Randomized Complete Block Design (RCBD) with two factors: AB Mix concentration (800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, and 1600 ppm) and LOF application (0 and 2 ml/l), resulting in 10 treatment combinations with three replications. Growth parameters measured included plant height (cm), number of leaves, leaf area (cm²), root volume (ml), and shoot-to-root ratio. Yield parameters included fresh weight (g) and dry weight (g). Results indicated that AB Mix concentration significantly affected plant height but had no significant impact on the number of leaves, leaf area, root volume, fresh weight, or dry weight. LOF application did not produce statistically significant effects on any measured parameters, although it showed a numerical trend toward increasing average values in most variables. Furthermore, the interaction between AB Mix concentration and LOF application did not significantly influence the growth or yield of pagoda mustard.